2002
DOI: 10.1016/s0304-3959(02)00010-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependency of analgesia elicited by intraoral sucrose in acute and persistent pain models

Abstract: Treatment of pain in newborns is associated with problematic drug side effects. Previous studies demonstrate that an intraoral infusion of sucrose and other sweet components of mother's milk are effective in alleviating pain in infant rats and humans. These findings are of considerable significance, as sweet tastants are used in pain and stress management in a number of clinical procedures performed in human infants. The ability of sweet stimuli to induce analgesia is absent in adult rats, suggesting that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 49 publications
6
65
2
2
Order By: Relevance
“…Thus, the absence of an analgesic response to sucrose in adults is apparently not due to the lowered sucrose preference observed in adults overall (Miller et al, 1994) and is consistent with animal model studies that revealed that sweet-induced analgesia progressively declines during development and is absent by the third week of life in the rat (Anseloni et al, 2002). Nevertheless, more research is warranted before one can conclude that sucrose is an ineffective analgesic during adulthood.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the absence of an analgesic response to sucrose in adults is apparently not due to the lowered sucrose preference observed in adults overall (Miller et al, 1994) and is consistent with animal model studies that revealed that sweet-induced analgesia progressively declines during development and is absent by the third week of life in the rat (Anseloni et al, 2002). Nevertheless, more research is warranted before one can conclude that sucrose is an ineffective analgesic during adulthood.…”
Section: Discussionsupporting
confidence: 84%
“…This eating-induced analgesia is distinct from the analgesia elicited by an acute intraoral infusion of sucrose (27)(28)(29) for two reasons. First, sucrose-induced analgesia is present only in infant rats (28). Second, eating-induced analgesia was evident when rats ingested laboratory chow, a food that contains no sugar or sucrose.…”
Section: Discussionmentioning
confidence: 87%
“…The irst observation of sucrose pain modulating efects was obtained by Blass et al 1987 who reported that contact with a small amount of sucrose solution on the tongue of infant rats rapidly increased the paw withdrawal latency (a measure of pain threshold) in a hot-plate test [56]. Sucrose-induced analgesia during infancy develops rapidly and persists for several minutes [57]. In addition, sucrose ingestion for a relatively long period of time produces analgesia [58,59].…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 99%
“…In addition, sucrose ingestion for a relatively long period of time produces analgesia [58,59]. Acute sucrose-induced analgesia is age-dependent that means it occurs mainly during the preweaning period in rats [57].…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 99%